Exploring the Potential as Molecular Quantum-Dot Cellular Automata of a Mixed-Valence ru2 Complex Deposited on a Au(111) Surface (Vol 10 Pg 2484 2023 - Montenegro-Pohlhammer, N (ROYAL SOC CHEMISTRY, 2024)
Correction for Exploring the potential as molecular quantum-dot cellular automata of a mixed-valence Ru2 complex deposited on a Au(111) surface by Nicolas Montenegro-Pohlhammer et al., Inorg. Chem. Front., 2023, 10, 2484-2492, https://doi.org/10.1039/D2QI02647C.